Artificial intelligence technology in internet financial edge computing and analysis of security risk. (16th March 2022) - Sun, Qi; Wu, Hong; Zhao, Binglong
This article mainly studies the application of artificial intelligence technology in internet finance edge computing and security risk analysis. This research treats the impact and specific application of artificial intelligence in internet finance as a system, analyses the relationship between the various elements in the system, and finds out countermeasures that can solve or reduce the negative impact it brings. The study found that the external technology risk score was 0.118, the industry-level risk score was 0.258, and the financial business risk score was 0.407. According to the 'maximum degree of membership' principle of the fuzzy comprehensive evaluation method, the maximum value is 0.407, which means that China's internet comprehensive score and financial risk level are at a relatively high level.